Retraction Note: Fixed point theorems for solutions of the stationary Schrödinger equation on cones - Gaixian Xue (SpringerOpen, 2020)
The Editors-in-Chief have retracted this article [1] because the results presented are invalid. The article also shows significant overlap with a number of previously published articles [2–5] and evidence of both peer review and authorship manipulation. The authors have not responded to any correspondence regarding this retraction.